Heavy Metals and PAHs in Meat, Milk, and Seafood From Augusta Area (Southern Italy): Contamination Levels, Dietary Intake, and Human Exposure Assessment - Di Bella, Calogero; Traina, Anna; Giosuè, Cristina; Carpintieri, Davide; Lo Dico, Gianluigi Maria; Bellante, Antonio; Del Core, Marianna; Falco, Francesca; Gherardi, Serena; Uccello, Maria Michela; Ferrantelli, Vincenzo (Frontiers in Public Health, 2020)
Heavy metals and PAHs were measured in animal foodstuffs from Augusta area in order to evaluate the potential human health risk associated to their consumption. All heavy metals were detected in seafood while most of the inorganic contaminants were <LOD in beef, pork and milks. Particularly, seafood registered higher values of total arsenic (As), mercury (Hg) and lead (Pb) than other food categories, while beef and pork showed higher content of zinc (Zn). Cadmium (Cd) and Pb were below the tolerable limits reported by the European Union in foodstuffs (Commission Regulation (EC) 1881/2006) except for mercury in seafood. Among the PAHs, chrysene (Chr) was detected in all terrestrial foodstuffs registering interesting content in raw milks, which presented also small quantity of benz(a)anthracene (BaA). The health risk for consumers was assessed for five age categories of consumers calculating the estimated weekly intake (EWI), the target hazard quotient (THQ) and the cancer risk (CR) for each element. Moreover, the margin of exposure (MOE) was estimated for PAHs. The seafood ingestion determined the EWIHg exceeding the PTWI recommended by the European Food Safety Authority, as well as the THQHg was >1 for baby, children and teenagers, indicating a non-carcinogenic risk for these age categories. The CRAs overcame 1*10-5 for all age categories and for elderly, by seafood and cow milk ingestions respectively, even further investigations are recommended on iAs in seafood. Moreover, the MOE showed a certain cancer risk for “baby” by cow milk ingestion.